Fifth formers of st. clare's - Blyton, Enid (Mammoth London, 1996)
The St. Clare's girls are now in the fifth form, shortly to go up into the sixth, but they are not too old for tricks and escapades, jokes and excitement. Especially amusing is French girl Antoinette who, like her sister Claudine, doesn't always understand the ways of St. Clare's.